Co-producing inclusive city-wide sanitation strategies: lessons from Chinhoyi, Zimbabwe. (April 2015) - Banana, Evans; Chitekwe-Biti, Beth; Walnycki, Anna
This paper explores how communities in Chinhoyi, Zimbabwe have used community-led mapping and enumerations (1) to build partnerships with local government to support the development and co-production of innovative pro-poor city-wide sanitation strategies as part of the SHARE City-Wide Sanitation Project. This action research project is being conducted in four cities across sub-Saharan Africa: Chinhoyi (Zimbabwe), Kitwe (Zambia), Blantyre (Malawi) and Dar es Salaam (Tanzania). This programme of work responds to the failure of conventional approaches to urban sanitation to meet the needs of low-income urban communities in sub-Saharan Africa. Over three years it has supported Shack/Slum Dwellers International affiliates to develop and test pro-poor sanitation strategies that can be adopted and driven by networks of community organizations and residents' associations, and supported by public authorities and private providers.